Relatório de Estágio Profissional "A motivação codificada" - Pedro Vieira Gomes (2017)
This document is framed in the curricular unit Practicum Training, included in the Physical Education Teacher Master´s degree in teaching Physical Education in Basic and Secondary Education. The internship is an opportunity to put into practice all the academic knowledge acquired during the academic training. This is the first contact with the school. The professional internship took place at the Agrupamento de Escolas dos Carvalhos (Gaia), with three student teachers, a cooperative teacher of this institution and a supervisor from the Faculty of Sport of the University of Porto. In addition to the pedagogical practice with the class, the student teacher participated in school sports activities and class management. The document entitled "Practicum Report" is divided into four major chapters: "Dimensão Pessoal", "Enquadramento da Prática Profissional", "Realização da Prática Profissional" and "Estudo de Investigação-ação". The objective of this theoretical construct is to account for and synthesize all the moments experienced by the trainee teacher throughout the traineeship year, specifying all the learning and knowledge acquired with a basis of support in the literature. It translates as a document revealing a personal and professional evolution of the trainee teacher demonstrating praises the courage, the pride and the passion of being a teacher